On the emergence of homochirality and life itself. (3rd February 2021) - Skolnick, Jeffrey; Gao, Mu
Abstract : Many of life's molecules including proteins are built from chiral building blocks. What drove homochiral building block selection? Simulations on demi-chiral proteins containing equal numbers of d - and l -amino acids show that they possess many modern homochiral protein properties. They have the same global folds and could do the same biochemistry, with ancient, essential functions being most prevalent. They could synthesize chiral RNA and lipids which formed vesicles. RNA eventually combined with proteins creating ribosomes for more efficient protein synthesis, and thus, life began. Increased native state stability from homochiral secondary structure hydrogen bonding helped drive proteins towards homochirality.